German-Danish or Danish-German? – A study of nationality adjectives in hyphenated compounds - Simonsen, Irene (Kalbotyra, 2024)
This study is an explicitly comparative linguistic analysis of attributive collocations with nationality adjectives in hyphenated compounds with dansk ‘Danish’ and deutsch ‘German’ as first or second element. In cultural studies of identity, migration, and minorities, as well as in Danish and German media debates, hyphenated compounds continuously raise questions: Could meaning be attributed to the hyphen? Is the first element separated from, connected with, or subordinated to the second element by the hyphen – or vice versa? The present study seeks to explore whether the order of national adjectives in hyphenated compounds carry meaning. The base word nouns are examined to see whether there are semantic differences between nouns modified by nationality adjectives with interchangeable order or fixed order. The study’s premise is that linguistic fixity and conventionality reflect fixed “Denkmuster” (‘patterns of thought’, Stein & Stumpf 2019, 193), also in collocations. The two Sketch Engine corpora, daTenTen20 and deTenTen18, serve as the empirical basis for the comparison. The study shows that quantitatively there is a clear preference for deutsch- or dansk- as the first element, but no general semantic differences can be observed between base words following compounds with adjectives in interchangeable order and those following compounds with adjectives in fixed order.